Konsep Masālik Al-‘Ilm Bi Maqāṣid Al-Sharī‘ah Perspektif ‘Abd al-Majīd an-Najjār: The Concept of Masālik al-‘Ilm bi Maqāṣid al-Sharī‘ah from the Perspective of ‘Abd al-Majīd an-Najjār - M. Tamlikhan; A Halil Thahir (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2026)
Maqāṣid al-Sharī‘ah serves as an epistemological framework that presents an understanding of Islamic law that is not solely text-oriented but also considers moral objectives, public welfare, and the surrounding social context. The purpose of this study is to comprehensively explain the concept of masālik al-‘ilm bi maqāṣid al-sharī‘ah by ‘Abd al-Majīd Al-Najjār, as this concept not only connects texts with reality but also integrates fundamental values of the Sharī‘ah. This research employs a qualitative method with a library research approach, based on the assumption that maqāṣid al-sharī‘ah cannot be determined through intuition, subjective tendencies, or rationality detached from the Qur’an and Sunnah, but must be formulated through valid and measurable scholarly pathways. Previous studies have focused only on substantive aspects such as the objectives of the Sharī‘ah and its classifications, but none have systematically examined the methodological mechanisms of how maqāṣid are known, verified, and scientifically validated. The findings indicate that masālik al-‘ilm bi maqāṣid al-sharī‘ah can be known through several main pathways: the pathway of commands and prohibitions, the pathway of scriptural explanations, the pathway of the Prophet Muhammad's practices, and the inductive pathway (istiqrā’). These four pathways complement each other in revealing the objectives of the Sharī‘ah, whether general, specific, or partial. Thus, this study positions maqāṣid al-sharī‘ah not merely as normative objectives of Islamic law but as an epistemological construct that must undergo measurable scientific procedures.Maqāṣid al-sharī‘ah serves as an epistemological framework that presents a legal understanding not solely oriented toward texts, but also considers moral objectives, public welfare, and the surrounding social context. This study discusses one concept within maqāṣid al-sharī‘ah, namely masālik al-‘ilm bi maqāṣid al-sharī‘ah, as a methodological framework for determining and understanding the objectives of Islamic sharia objectively and based on revelation. This research employs a qualitative method with a library research approach, starting from the assumption that maqāṣid al-sharī‘ah cannot be determined based on intuition, subjective tendencies, or rationality detached from the Qur’an and Sunnah, but must be formulated through valid and measurable scholarly paths. By referring to the thoughts of ‘Abd al-Majīd an-Najjār, this study aims to explain the urgency of masālik as an epistemological instrument to maintain the validity of maqāṣid and prevent its misuse in ijtihad practices, especially in addressing continuously evolving contemporary issues. The study results indicate that masālik al-‘ilm bi maqāṣid al-sharī‘ah encompasses several main paths, namely: the path of commands and prohibitions, the path of nash explanation, the path of the Prophet Muhammad's practices, and the inductive path (istiqrā’). These four paths complement each other in revealing the objectives of sharia, whether general, specific, or partial. Through the application of these masālik, maqāṣid al-sharī‘ah can be understood systematically, consistently, and in harmony with the overall structure of sharia.